2018
DOI: 10.1136/jnnp-2018-318568
|View full text |Cite
|
Sign up to set email alerts
|

Burden of rare variants in causative genes for amyotrophic lateral sclerosis (ALS) accelerates age at onset of ALS

Abstract: ObjectivesTo evaluate the burden of rare variants in the causative genes for amyotrophic lateral sclerosis (ALS) on the age at onset of ALS in a Japanese case series.MethodsWe conducted whole-exome sequencing analysis of 89 families with familial ALS (FALS) and 410 patients with sporadic ALS (SALS) to identify known pathogenic mutations or rare functionally predicted deleterious variants in the causative genes for ALS. Rare variants (minor allele frequency <1%) with scaled Combined Annotation-Dependent Depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 30 publications
3
39
1
Order By: Relevance
“…It is important to note that the percentage of co-occurrence of gene variants estimated by our study is higher as compared with most of the previous studies, including a recent large-scale study, identifying oligogenity in 1% of ALS patients [75]. The reported frequencies of patients with multiple variants in ALS are indeed varied, having been estimated in previous studies as 1.6% [15], 1.3% [76], 1.4% [72], 3.8% [8], 7.9% [73], 18.8% [17], and 19.5% [71]. These differences reflect a number of methodological issues such as the number and selection of sequenced genes (i.e., gene size effect or genetic variability of studied genes), presence of controls, and criteria adopted for filtering and, most importantly, for predicting the pathogenicity of identified variants.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…It is important to note that the percentage of co-occurrence of gene variants estimated by our study is higher as compared with most of the previous studies, including a recent large-scale study, identifying oligogenity in 1% of ALS patients [75]. The reported frequencies of patients with multiple variants in ALS are indeed varied, having been estimated in previous studies as 1.6% [15], 1.3% [76], 1.4% [72], 3.8% [8], 7.9% [73], 18.8% [17], and 19.5% [71]. These differences reflect a number of methodological issues such as the number and selection of sequenced genes (i.e., gene size effect or genetic variability of studied genes), presence of controls, and criteria adopted for filtering and, most importantly, for predicting the pathogenicity of identified variants.…”
Section: Discussioncontrasting
confidence: 64%
“…In our cohort, about 15% of patients were harboring variants in at least two of the investigated genes, confirming the findings of previous studies and supporting the hypothesis that rare variant burden can play a role in the multistep model of disease. Such a model would be inclusive of patients with mutations in major ALS genes [8,15,17,57,[71][72][73], even if for such genes as C9orf72, SOD1, TARDBP and FUS a reduced number of pathogenetic steps has been recently suggested [74]. It is important to note that the percentage of co-occurrence of gene variants estimated by our study is higher as compared with most of the previous studies, including a recent large-scale study, identifying oligogenity in 1% of ALS patients [75].…”
Section: Discussionmentioning
confidence: 62%
“…It means that pathogenic variants in different genes may be needed to fully express the disease. The burden of rare variants could modify the phenotype [ 159 ], influencing the age at onset, which is anticipated in patients with multiple variants [ 160 , 161 ] and could have an impact on survival [ 162 ].…”
Section: The Complex Genetic Architecture Of Als and The Challengementioning
confidence: 99%
“…Additionally, discrete ALS phenotypes such as flail arm or flail leg demonstrate a slower disease course compared to classic "Charcot"-like forms [6]. Large-scale whole-exome sequencing studies showed that the age of onset or survival in ALS patients might be influenced by several genetic variants [7,8]. A general assumption is that the disease results from a complex interplay between genetic and environmental factors, with involved genes clustering into three major categories, namely protein homeostasis, RNA homeostasis/processing, and cytoskeletal dynamics, and immune dysregulation having a major role in determining disease onset and progression [9,10].…”
Section: Introductionmentioning
confidence: 99%